Pengaruh Kecepatan Putaran Pada Proses Rotary Alga Biofilm Reactor (RABR) Untuk Penyisihan COD Menggunakan Mikroalga Chlorella sp. Pada Limbah Cair Domestik - Mutia Nurrahmadhani; Shinta Elystia; Sri Rezeki Muria (Jurnal Online Mahasiswa (JOM) Bidang Teknik dan Sains, 2020)
Domestic liquid waste has organic matter and high pollutant load. Microalgae Chlorella sp. is able to utilize organic material as a source of nutrition for its growth, hence it may reduce pollutant of domestic liquid waste. Microalgae Chlorella sp. which grows on the surface of the disk is suspended in domestic liquid waste using a Rotary Alga Biofilm Reactor (RABR) is able to absorb high level nutrient, so that they have high cell growth. In this research, it is conducted by using speed rational variations in RABR process (2, 4, dan 6 rpm) and contact time (0, 1, 3, 5, 7 days) to remove COD parameters. Based on the results toward the removal of pollutant parameters by using 4 rpm rotational speed variation is higher than using 2 and 6 rpm. The concentration of COD removal of 210 mg/L with the removal efficiency of 73,08 %.Keywords: Chlorella sp, COD, Rotation Speed, Domestic Liquid Waste, Rotary Alga Biofilm Reactor (RABR)